KONSTRUKSI SOSIAL DALAM REALITAS SOSIAL - Charles R. Ngangi (AGRI-SOSIOEKONOMI, 2011)
Social institutions are studied by social constructions include religion, family, marriage, gender,"sick" psychological etc. From the perspective of social construction, it can be explained that it is impossiblefor someone to remove the phenomenon occurs in the community, and a process of internalizationmay be able to give an influence to someone.The ability in determining the weight or lightness of the existence of nature of the characteristics andphenomena that exist with the externalization process itself will form an objective reality. In this processone can put himself into the intersubjective world view. Where in the view of a world that can produce aprocess is objectivity on a process of meaningful subjective.